Study of Fetomaternal Outcome of Teenage Pregnancy - Sanobar Baloch, Sumaiya Farooq, Shazia Awan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Everywhere in the globe, the issue of teenage pregnancies is a major public health problem. Pregnant girls and their fetuses are at high risk for a range of health difficulties that are hard to overcome, including physical, social, and medical issues. Aim: To find out how teenage pregnancy affects the fetomaternal outcome. Methodology: Retrospective research was done at Indus Medical Collage, Tando Muhammad Khan for six months. A total of 260 pregnant teens were chosen for the study. Researchers looked at data on the prevalence, ages, parities, booking status, levels of education and socioeconomic position, as well as medical conditions, labour issues, delivery methods, and newborn outcomes. Results: There were 260 pregnant adolescent girls in this group. As a result, 5.56 % of adolescent pregnancies occurred. 216 (83.46%) of the 260 adolescent pregnant women were 19 years old, while 43 (16.53 %) were 18 years old. 7 (2.69%) of women had a first-trimester abortion, 3 (1.15%) had a second-trimester abortion, and 2 had an ectopic pregnancy (0.76 5 ). Teen pregnancy problems include preterm labor 52 (20%) and Cephalon Pelvic Disproportion 40 (15.38%) as well as fetal distress 31 (11.92%) and obstructed labor 9 (3.46 %). Neonatal complications in teenage pregnancy preterm babies 56(21.53 %), low birth weight babies<2.5kg 81 (31.15%), 72 (27.69 %) NICU admission, perinatal death 8 (3.07 %). Conclusion: Due to the greater risk of complications during childbirth that is connected with pregnancies in adolescence, mothers and children in the United States may get additional attention from the nation's health care systems.